Species of Fish in rivers in the Northern Peninsula of Sulawesi Island - Bataragoa, Nego Elvis; Kambey, Alex D. (Sam Ratulangi University, 2021)
This study aims to determine the species of fish found in the Poigar River, Ranoyapo River, Maruasey River, Talawaan River, and Likupang River in the northern peninsula of Sulawesi Island. These five rivers empty into the Sulawesi Sea. Sampling was carried out in the upstream, middle and downstream parts of the river, all sampling areas were freshwater areas, estuary areas with brackish water types were not included in this study. Sampling was carried out using cast nets and electric shocks. There are 58 species (16 orders, 21 families, 40 genera). Families Gobidae (9 genera, 19 species) and Eleotridae (8 genera 13 species), 19 other families have only 3 or 2 or 1 species. There are 28 species of Ranoyapo River, 25 species of Maruasey River, 23 species of Poigar River, 15 species of Likupang River, and 9 species of Talawaan River. Eel Anguilla marmorata widely distributed in five rivers, and Eleotris melanosoma (Eleotridae) Osteochilus hasseltii (Cyprinidae) in four rivers. The other species are only found in 3, 2, and 1 rivers. There are 27 species found in only one river.Keywords: Freshwater; River; Species; Fish.AbstrakPenelitian ini bertujuan untuk mengetahui spesies ikan yang terdapat di Sungai Poigar, Sungai Ranoyapo, Sungai Maruasey, Sungai Talawaan dan Sungai Likupang di semenanjung utara Pulau Sulawesi. Lima sungai ini bermuara di Laut Sulawesi. Pengambilan sampel dilakukan pada bagian hulu, tengah dan bagian hilir sungai, seluruh wilayah pengambilan sampel adalah wilayah air tawar, daerah muara dengan tipe air payau tidak termasuk dalam penelitian ini. Pengambilan sampel dilakukan dengan menggunakan jaring lempar dan kejutan listrik. Terdapat 58 spesies (16 ordo, 21 famili, 40 genus). Famili Gobidae (9 genus, 19 spesiies) dan Eleotridae (8 genus 13 spesies), 19 Famili yang lain hanya memiliki 3 atau 2 atau 1 spesies. Sungai Ranoyapo terdapat 28 spesies, Sungai Maruasey 25 spesies, Sungai Poigar 23 spesies, Sungai Likupang 15 spesies dan Sungai Talawaan 9 spesies. Ikan sidat Anguilla marmorata menyebar luas pada lima sungai, dan Eleotris melanosoma (Eleotridae) Osteochilus hasseltii (Cyprinidae) pada empat sungai. Spesies yang lain hanya ditemukan pada 3, 2 dan 1 sungai. Terdapat 27 spesies yang ditemukan hanya pada satu sungai.Keywords: Freshwater; River; Species; Fish.